Heterosemy of case markers and clause-linkers in Andaandi (Nile Nubian) - Angelika Jakobi (LibraryPress@UF, 2016)
Case markers are usually associated with nouns or noun phrases but, as shown in Aikhenvald’s (2008) cross-linguistic study on “versatile cases”, case markers are also used as clause-linkers in a wide range of genetically diverse languages. However, African languages are not found in Aikhenvald’s sample. Our paper shows that in some subgroups of Nilo-Saharan and Afro-Asiatic case markers are, in fact, attested on subordinate clauses. Focusing on Andaandi, a Nubian language classified as a member of the Eastern Sudanic subgroup of Nilo-Saharan, we first present an outline of the system of grammatical relations and an overview over the use of core and peripheral case markers on noun phrases. This overview serves as a background for our study of case markers. While the Accusative case marker is employed as subordinator of object complement clauses, various peripheral case markers are used as subordinators of adverbial clauses. The different morphosyntactic contexts in which the case markers occur, i.e. on noun phrases and on verbs of subordinate clauses, determine their functional change and heterosemy.